Lasok's European Court practice and procedure - Lasok, K.P.E. (London [England] : Bloomsbury Professional, 2022)
"When the European Court of Justice and the Court of First Instance drafts its own procedural rules, and when it makes decisions on procedural matters, it turns to the highly regarded Lasok's European Court Practice and Procedure for confirmation and guidance. Fully revised and updated the fourth edition: 1. Explains the implications of Brexit and the residual jurisdiction of the ECJ in relation to the UK under the Withdrawal Agreement. 2. Takes account of and provide in-depth analysis of all case law since the previous edition. 3. Provides guidance on the new General Court Rules of Procedure. 4. Provides new commentary on the Judges and Advocates General caused by Brexit and the current ongoing litigation concerning Advocate General Sharpston. 5. Includes additional commentary on the confidentiality regime for cases raising security concerns. Written by the internationally acknowledged expert in this area of law Lasok's European Court Practice and Procedure is the leading and must have work for anyone preparing a case to be heard before the European Court of Justice."--
Chapter 1 Judicial institutions and bodies -- Chapter 2 General outline of procedure -- Chapter 3 Parties -- Chapter 4 Representation and legal aid -- Chapter 5 Intervention -- Chapter 6 Procedural issues -- Chapter 7 Admissibility -- Chapter 8 Interim relief -- Chapter 9 Pleading -- Chapter 10 Evidence -- Chapter 11 Measures of enquiry -- Chapter 12 Exclusion of evidence -- Chapter 13 Rules of evidence -- Chapter 14 Costs -- Chapter 15 Appeals and review procedures -- Chapter 16 Judgments and decisions of the Court -- Chapter 17 Forms of action -- Appendices -- Appendix 1 Table of concordance of treaty provisions concerning the Court -- Appendix 2 List of international conventions and agreements conferring jurisdiction on the Court -- Appendix 3 Protocol on the Statute of the Court of Justice of the European Union -- Appendix 4 Rules of Procedure of the Court of Justice -- Appendix 5 Supplementary Rules of the Court of Justice -- Appendix 6 Decision of the Court of Justice of 23 October 2012 concerning the judicial functions of the Vice-President of the Court (2012/671/EU) -- Appendix 7 Decision of the Court of Justice of 13 September 2011 on the lodging and service of procedural documents by means of e-Curia (2011/C 289/06) -- Appendix 8 Recommendations to national courts and tribunals in relation to the initiation of preliminary ruling proceedings (2012/C 338/01) -- Appendix 9 Practice Directions to parties concerning cases brought before the Court -- Appendix 10 Rules of Procedure of the General Court -- Appendix 11 Decision of the General Court of 14 September 2011 on the lodging and service of procedural documents by means of e-Curia (2011/C 289/07) -- Appendix 12 Practice Rules for the Implementation of the Rules of Procedure of the General Court 1569 -- Appendix 13 Legal Aid Form General Court -- Appendix 14 Rules of Procedure of the European Union Civil Service Tribunal -- Appendix 15 Decision of the Civil Service Tribunal No 3/2011 taken at the Plenary Meeting on 20 September 2011 on the lodging and service of procedural documents by means of e-Curia (2011/C 289/08) -- Appendix 16 Instructions to the Registrar of the European Union Civil Service Tribunal of 21 May 2014 -- Appendix 17 Practice Directions to Parties on Judicial Proceedings before the European Union Civil Service Tribunal of 21 May 2014 -- Appendix 18 Guide for Legal Aid Applicants and Standard Form of Application for Legal Aid -- Appendix 19 e-Curia: Conditions of use applicable to parties' representatives -- Appendix 20 e-Curia: Conditions of use applicable to assistants
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Procedure (Law) -- European Union countries; Electronic books